2021
DOI: 10.1371/journal.pone.0257722
|View full text |Cite
|
Sign up to set email alerts
|

A prospective population-based multicentre study on the impact of maternal body mass index on adverse pregnancy outcomes: Focus on normal weight

Abstract: Background Maternal body mass index (BMI) below or above the reference interval (18.5–24.9 kg/m2) is associated with adverse pregnancy outcomes. Whether BMI exerts an effect within the reference interval is unclear. Therefore, we assessed the association between adverse pregnancy outcomes and BMI, in particular within the reference interval, in a general unselected pregnant population. Methods Data was extracted from a prospective population-based multicentre cohort (Risk Estimation for PrEgnancy Complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…They demonstrated that gestational hypertension, gestational diabetes and pre-eclampsia increased steadily with increasing body mass index. 16 Our study also demonstrated that obese women had bigger babies when compared with their non-obese counterparts (Table 4). There is also increased number of caesarean sections among women with increased Body Mass Index when compared with non-obese women in our participants.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…They demonstrated that gestational hypertension, gestational diabetes and pre-eclampsia increased steadily with increasing body mass index. 16 Our study also demonstrated that obese women had bigger babies when compared with their non-obese counterparts (Table 4). There is also increased number of caesarean sections among women with increased Body Mass Index when compared with non-obese women in our participants.…”
Section: Discussionsupporting
confidence: 63%
“…This is also similar to the finding by study by Van Der Linden et al that demonstrated strong associations between obesity and these conditions. 15 Van Hoorn F. et al 16 also examined high maternal weight status and complications during pregnancy and delivery, where they also found that overweight or obesity during pregnancy was associated with increased odds of several adverse pregnancy and delivery complications. They demonstrated that gestational hypertension, gestational diabetes and pre-eclampsia increased steadily with increasing body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation